Adoption Gap Analysis in Tomato Cultivation in Banda District of Bundelkhand (U.P.) - Gupta, B K; Dwivedi, S. V.; Mishra, B. P.; Mishra, Dheeraj; Ojha, Pankaj K.; Verma, A. P.; Kalia, Abhishek (Indian Journal of Extension Education, 2021)
Bundelkhand area of Uttar Pradesh is comprised of seven districts viz., Chitrakoot, Banda,Â Hamirpur, Mahoba, Jalaun, Jhansi and Lalitpur. The present study was conducted in Banda district of Uttar Pradesh where the vegetable crops are grown by farmers in large areas.Â Among the eight blocks of Banda, two blocks namely Badokhar Khurd and Mahua were purposively selected. Eight vegetable growing villages (4 from Badokhar Khurd and 4 from Mahua block) based on production potential of the tomato were drawn up and from eachÂ village 18 vegetable growers (six from each category) having minimum 3 years of experience in commercial tomato cultivation were selected randomly with sample size is 144. It is revealed that technological gap in marginal farmers category was observed in the nurseryÂ raising and seed-treatment (74.80%) followed by plant protection measures (67.83%) and fertilizer application (67.00%). In small farmers category Identification of insect and pest (77.16%) followed by fertilizer application (74.50%) and plant protection measuresÂ (67.33%) were major whereas for medium category the technological gap was observed in nursery raising and seed-treatment (69.30%) followed by plant protection measuresÂ (67.58%) and fertilizer application (66.17%). The technological gap level in all categoriesÂ of farmers revealed that the medium level of technological gap was observed in majority of tomato growers (44.45%) followed by high level of technological gap (38.20%) and lowÂ level of technological gap (17.36%).